Sustainable tourism in National Park "Đerdap", Serbia - attitudes of local population - Brankov Jovana; Jovičić Dobrica; Milijašević Dragana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
In the context of the broader controversy about sustainable development, tourism literature highlights the importance of the support of the local population to tourism development. The active support of the community is essential for the local government, the future development policies and all entities that participate in the creation of sustainable tourism development. The specific dimension of this influence exists in protected areas, given the pronounced strong environmental component and a bond that is created among tourism - protected area - locals. The paper analyzes the attitudes and opinions of the local population residing in the National Park “Đerdap” or its protection zone about the effects and control of tourism development, as well as the availability of information on sustainable tourism and the impact this activity has on the community. The method applied is survey research on a sample of 227 respondents. During the preparation of the survey, the methodological procedure for the analysis of sustainable tourism indicators ware used proposed by the World Tourism Organization. [Projekat Ministarstva nauke Republike Srbije, br. 47007 III]